2016
DOI: 10.1245/s10434-016-5275-3
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Trial Exploring the Success of Cryoablation Therapy in the Treatment of Invasive Breast Carcinoma: Results from ACOSOG (Alliance) Z1072

Abstract: Background Cryoablation is a well-established technique to treat fibroadenomas. Pilot studies suggest this could be an effective non-surgical treatment for breast cancer. American College of Surgeons Oncology Group (ACOSOG) Z1072 is a phase II trial exploring the effectiveness of cryoablation in the treatment of breast cancers. Methods The primary endpoint of Z1072 was the rate of complete tumor ablation, defined as no remaining invasive breast cancer (IBC) or ductal carcinoma in situ (DCIS) on pathologic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 18 publications
1
78
0
Order By: Relevance
“…This requires ultrasound-guided positioning of only one needle. Under these problematic conditions, local tumor control could be achieved in 92 % of cases with the result being significantly better in small tumors up to 1 cm than in larger tumors [49]. Another study showed local control of 76.9 % of breast carcinomas up to 3 cm after 12 months.…”
Section: Breastmentioning
confidence: 99%
“…This requires ultrasound-guided positioning of only one needle. Under these problematic conditions, local tumor control could be achieved in 92 % of cases with the result being significantly better in small tumors up to 1 cm than in larger tumors [49]. Another study showed local control of 76.9 % of breast carcinomas up to 3 cm after 12 months.…”
Section: Breastmentioning
confidence: 99%
“…A total of 63 articles matched the selection criteria. The 63 articles included 16 feasibility studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], 12 phase I studies [29][30][31][32][33][34][35][36][37][38][39][40], nine phase II studies [41][42][43][44][45][46][47][48][49], three comparative studies [50][51][52], one retrospective study [53], and four randomised controlled trials [54][55][56]. In 18 studies the type of study was not reported [8,[57][58][59][60][61][62][63][64]…”
Section: Selected Studiesmentioning
confidence: 99%
“…In five studies [21,24,49,59,63], patients withdrew from the study during or after treatment and in another six studies [15,26,44,48,49,72] patients withdrew before the start of the treatment. The overall STROBE score ranged from four to seven (mean…”
Section: Quality Assessmentmentioning
confidence: 99%
“…MRI has had the greatest success in accomplishing this goal. Post-cryoablation detection of residual tumor by MRI has been reported with a negative predictive value of 92% [7].…”
mentioning
confidence: 99%